Comparative morphology of Sarawak species of The Limnonectes Kuhlii Complex - Izneil Nashriq, Mohammad Nasir (Universiti Malaysia Sarawak (UNIMAS), 2015)
The study focuses on the identification of the Sarawak species of the Limnonectes kuhlii complex through comparative morphology. Commonly known as Kuhl's creek frog, it is a species complex in which the lineages are not yet been described. With its wide geographical distribution raging from the Southern Yunnan and Guangxi province in China and throughout Southeast Asia (McLeod, 2010), they exhibit strong male-biased sexual dimorphism, unusual secondary sexual dimorphism and a great deal of phenotypic similarity (McLeod, 2008). The objective of the study is to distinguish the Limnonectes kuhlii complex of Sarawak based on morphology and morphometric variables and also to construct a framework of taxonomic description for the identification of the Bornean Limnonectes kuhlii complex. Through Discriminate Function Analysis (DFA) and Cluster Analysis (CA) the character that is able to discriminate the species complex are of ED/HL, FOL/ SVL and morphological characters which are pigmentation on chest throat, pigmentation on lower mouth part and tubercles on cloaca.